Estudo da adsorção de hidrogênio e sulfeto na superfície de paládio: aspectos experimentais (eletroquímica) e teóricos (ab initio e Teoria do Funcional da Densidade) - Ângelo, Antônio Carlos D. [UNESP]; Souza, Aguinaldo Robinson de [UNESP]; Morgon, Nelson H.; Sambrano, Julio Ricardo [UNESP] (Sociedade Brasileira de Química, 2001)
The adsorption of H and S2- species on Pd (100) has been studied with ab initio, density-functional calculations and electrochemical methods. A cluster of five Pd atoms with a frozen geometry described the surface. The computational calculations were performed through the GAUSSIAN94 program, and the basis functions adapted to a pseudo-potential obtained by using the Generator Coordinate Method adapted to the this program. Using the cyclic voltammetry technique through a Model 283 Potentiostat/Galvanostat E.G.&G-PAR obtained the electrochemical results. The calculated chemisorption geometry has a Pd-H distance of 1.55Å, and the potential energy surface was calculated using the Becke3P86//(GCM/DFT/SBK) methodology. The adsorption of S2- ions on Pd surface obtained both through comparison between the experimental and theoretical results, at MP2 level, suggest a S2- absorption into the metallic cluster. The produced Pd-(S2-) system was show to be very stable under the employed experimental conditions. The paper has shows the powerful aid of computational methods to interpret adsorption experimental data.
Experimental (electrochemistry) and theoretical (ab initio and Density Functional Theory) studies of hydrogen and sulfide adsorption on palladium (100) surface
Keywords: ab initio; DFT; cyclic voltammetry; adsorption; hydrogen; sulfide